The Effect of SMS Reminders on Adherence in a Self-Guided Internet-Delivered Intervention for Adults With ADHD - Nordby, Emilie S.; Gjestad, Rolf; Kenter, Robin M. F.; Guribye, Frode; Mukhiya, Suresh K.; Lundervold, Astri J.; Nordgreen, Tine (Frontiers in Digital Health, 2022)
Background: Self-guided Internet-delivered interventions may serve as an accessible and flexible non-pharmacological treatment supplement for adults with ADHD. However, these interventions are challenged by low adherence. Objective: To examine whether weekly SMS reminders improve adherence to a self-guided Internet-delivered intervention for adults with ADHD. Method: The study used a multiple randomized trial design where the participants who had not completed their weekly module within two days were randomized to either receive or not receive an SMS reminder. The primary outcome was adherence, defined as module completion, logins, time spent on intervention, and self-reported practice of coping strategies. Results: A total of 109 adults with a self-reported ADHD diagnosis were included in the study. The results showed that SMS reminders were associated with an increased likelihood of login within 48 hours during the second module of the intervention, but not for the remaining modules. Moreover, receiving an SMS reminder was associated spending more time on the modules and faster login time in module three and five, specifically. However, the overall results did not show an effect of SMS reminders on module completion, number of logins and practice of coping strategies. Conclusion: The results showed that SMS reminders do not improve number of logins, module completion rates or practice of coping strategies, but they may lead to faster login time and more time spent on the modules. To utilize the potential of self-guided Internet-delivered intervention in making non-pharmacological accessible for adults with ADHD, new methods to facilitate meaningful engagement should be developed and tested.